2019
DOI: 10.5965/223811711812019222
|View full text |Cite
|
Sign up to set email alerts
|

Teores e estoques de carbono orgânico do solo em diferentes usos da terra no Planalto Sul de Santa Catarina

Abstract: O estudo das modificações do carbono do solo provocadas pela mudança de uso da terra possibilita adotar medidas que reduzam os riscos de futuros impactos negativos. O objetivo da pesquisa foi quantificar e comparar os teores (COT) e os estoques (EC) de carbono orgânico total do solo em diferentes usos da terra na região do Planalto Sul de Santa Catarina. Foram selecionadas áreas sob floresta natural (FN), plantio de pinus (PP), campo natural pastejado (CP) e sucessão de lavoura e pastagem (LP). Amostras de sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(11 reference statements)
1
4
0
1
Order By: Relevance
“…Therefore, monitoring the microbiological quality indexes of the systems (Table 3), the carbon of the microbial biomass (CMB) differed significantly for the systems, with the highest average found in CS with a value of 425.54 mg kg -1 of C, with a decrease of 55% for FPS and 68% for PS. Similar behavior was found by Santos et al (2019) studying several land uses in a semiarid environment, where the highest value of CMB was found in the dry tropical forest, however the difference between the means was smaller when the Caatinga areas were converted to trees and intercropped systems. Assis et al (2019), state that the non-revolving soil contributes to higher levels of CMB in the soil, preserving fungal hyphae and root systems.…”
Section: Microbiological Activitysupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, monitoring the microbiological quality indexes of the systems (Table 3), the carbon of the microbial biomass (CMB) differed significantly for the systems, with the highest average found in CS with a value of 425.54 mg kg -1 of C, with a decrease of 55% for FPS and 68% for PS. Similar behavior was found by Santos et al (2019) studying several land uses in a semiarid environment, where the highest value of CMB was found in the dry tropical forest, however the difference between the means was smaller when the Caatinga areas were converted to trees and intercropped systems. Assis et al (2019), state that the non-revolving soil contributes to higher levels of CMB in the soil, preserving fungal hyphae and root systems.…”
Section: Microbiological Activitysupporting
confidence: 81%
“…In this system, the lowest levels of carbon storage in the soil occurred, at depth 0 -10 cm, and its reduction was 57% when compared to the system with preserved vegetation. Santos et al (2019) studying the stocks of organic carbon in different land uses in Santa Catarina, also found the highest averages in the superficial layers of the soil, decreasing along the depth, with native vegetation being the one with the highest average, differing statistically from the other types of land use. Pegoraro et al (2018) comparing soil carbon and nitrogen stock levels in different types of use in the semiarid region, also found the highest averages for the native forest environment, attributing these values to a greater accumulation of dry matter from plant residues on the surface of the ground.…”
Section: Carbon and Nitrogen Stocksmentioning
confidence: 96%
“…Observing the spatial behavior of the TOC, it appears that the highest levels of this attribute are inverse to the highest levels of density. Luciano et al (2010) andSchroeder et al (2017) observed that these attributes have a significant inverse relationship, as the higher the organic carbon content, the lower the density of the soil. The EST.…”
Section: Resultsmentioning
confidence: 99%
“…The balance between the input and output of carbon (C) from the soil has strong influences on atmospheric CO 2 concentrations, and the form of land occupation and management can affect this natural process by modifying the flow of CO 2 from the soil to the atmosphere (emission) or from the atmosphere to the ground (sequestration). Thus, there is a growing interest in promoting C sequestration in agricultural soils as a way to mitigate the increasing CO 2 levels in the atmosphere (Santos, 2019). The more C is stored in the soil in the form of organic matter, the more life there is in the soil, the greater the retention of moisture, and the more nutrients are available to the plants.…”
Section: Mandalamentioning
confidence: 99%